2017
DOI: 10.1038/s41598-017-14002-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the Cholesterol-dependent Binding of Perfringolysin O-based Probes and Cell Membranes

Abstract: Cholesterol distribution in the cell is maintained by both vesicular and non-vesicular sterol transport. Non-vesicular transport is mediated by the interaction of membrane-embedded cholesterol and water-soluble proteins. Small changes to the lipid composition of the membrane that do not change the total cholesterol content, can significantly affect how cholesterol interacts with other molecules at the surface of the membrane. The cholesterol-dependent cytolysin Perfringolysin O (PFO) constitutes a powerful too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 53 publications
2
30
0
Order By: Relevance
“…Considering vesicle shedding as a pure membrane repair process should be carefully reassessed. On the other hand, CDCs are also used as model tools in other biology fields 22 , as cholesterol-binding probes 23 . Thus, understanding the differences in the membrane behavior of CDC toxins is also critically important for the interpretation of the experimental results, obtained with their help.…”
Section: Discussionmentioning
confidence: 99%
“…Considering vesicle shedding as a pure membrane repair process should be carefully reassessed. On the other hand, CDCs are also used as model tools in other biology fields 22 , as cholesterol-binding probes 23 . Thus, understanding the differences in the membrane behavior of CDC toxins is also critically important for the interpretation of the experimental results, obtained with their help.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of a water-soluble PFO monomer to the membrane is diffusional and electrostatic interactions may play a role since it has been observed that the introduction or elimination of charged residues alters binding [ 12 , 16 , 24 , 25 , 49 ]. While on the membrane surface, insertion of non-polar and aromatic amino acids, and/or specific interactions with membrane lipids, help to anchor the protein to the membrane [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, T490 in the PFO-cholesterol model is predicted to be involved in a complex H-bonding network involving both its side chain and backbone carbonyl and the side chains of T460 and E458 (in its protonated form) from the undecapeptide. The static model, however, does not provide a simple explanation for the adjacent L491S mutation that does not significantly change the cholesterol-binding of PFO [ 25 ]. This implies a newly found H-bonding role for the Ser side chain at this position that, in contrast with the reduced affinity observed for the L491A substitution, conserved the affinity of PFO for cholesterol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HeLa cells incubated with P. aeruginosa were washed to remove unbound bacteria, and permeabilized using a Cys-less derivative of perfringolysin O (rPFO). rPFO is a pore-forming toxin that only perforates mammalian cell membranes due to its specificity for cholesterol (30,31). We used antibodies against glyceraldehyde-phosphate dehydrogenase (GAPDH) and Na ϩ /K ϩ -ATPase to detect cytosolic and plasma membrane fractions, respectively (Fig.…”
Section: Popb-assisted Popd Insertion Into Cell Membranesmentioning
confidence: 99%